Fire risk analysis and mapping in Kepulauan Seribu, North Jakarta, Indonesia - Nazhrah, Siti Widya; Lestari, Fatma; Octaviani, Devie Fitri (Universitas Gadjah Mada, 2022)
Purpose: Kepulauan Seribu is an inseparable part of DKI Jakarta Province. Kepulauan Seribu has more than 110 islands and 11 inhabited islands, where this island area has its own challenges to fire response time. The objective of this study is to measure the fire risk in Kepulauan Seribu, North Jakarta. Method: The data collection was carried out by means of stratified sampling and cross-sectional using a list of questionnaires and focus group discussion (FGD). The instrument used for the FGD with the Local Government Fire Service of Jakarta was a selected document with three parts; hazard, vulnerability, and risk management or fire protection and has twenty-two questions on a scale of one to five. The questionnaire on community leaders used customized questions on a scale of one to three. The results of both instruments were analyzed univariate and overlaid with the map of Kepulauan Seribu. Results: The results from both areas consisting of six urban villages and twenty-four community units showed that the locations with the highest risk of fire were located at Kelapa Island Urban Village at the high level, while the other five urban villages had a moderate risk. The most influential aspect of the high level of fire risk in Kepulauan Seribu was the dimensions of risk management and fire protection. Conclusion: The lack of infrastructure and fire fighting equipment were two important factors in the high risk of fire. The condition of the islands provides a significant difference in the source of the danger to fire, which one of the fire causes was autoignition. Suggestions that could be given are increasing the awareness and active roles of the community in fire control and prevention, managing training and socialization undertaken by the local communities and conceiving provision of infrastructure that supports fire prevention and control, transportation, and fire station.